Deteksi Foto Komposit Berdasarkan Perbandingan Pantulan Cahaya Pada Mata Dengan Pendekatan Pixel-Based - Prastyawan Aji Nugraha; Rimba Whidiana Ciptasari; Bambang Pudjoatmodjo (eProceedings of Engineering, 2015)
There are several types of photo manipulation. For example, combining objects from different sources into a single image which is often reffered to as photo composite. One of outstanding work dealing with photo composite has been developed by Micah K. Johnson and Hany Farid. They estimated the light source through the reflection specular highlights recorded on the eyes. Our proposed work exploits different approach which is pixel-based, to detect photo composite. Our method contains comparative characteristics of the amount of reflected light using EulerNumber, the reflection area using outer line capturing, and the formation of light between objects recorded in the human eye in an image by comparing the distance between the reflection of light. The experimental result described that the accuracy of the proposed work reach 98% depicted by ROC curve with Area Under ROC Curve (AUC) reach 0.9304. The results fall into Excellent Classification. Keywords : Image Forensics, Specular Highlight, Digital Forensics, Composites Image.